Association of waterpipe smoking and road traffic crashes - Karbakhsh Mojgan; Saadat Soheil (BMC, 2010)
Abstract Background The purpose of this research was to examine whether waterpipe smokers experience increased risk of motor vehicle crashes. Methods In a telephone survey, a random sample of Iranian drivers were asked to report their age, gender, vehicle age, whether their vehicles were equipped with anti-lock braking system (ABS), average daily drive time (DDT), whether they smoked cigarette or waterpipe, whether they had diabetes mellitus (DM), number of traffic crashes during the last calendar year and whether the crash involved a pedestrian or another vehicle. Results A total of 2070 motor vehicle owners with the mean age of 41.6 ± 11.45 were interviewed. The annual incidence of Road Traffic Crashes (RTC) was 14.9%; 14.0% involved a collision/s with other vehicles and 0.9% with pedestrians. There was an association between the RTC and male gender, DDT, being a cigarette smoker, being a waterpipe smoker and DM in univariable analysis. The association between RTC and being a waterpipe smoker and also cigarette smoker was significant in multivariable analysis after adjustment for DDT. Conclusions Being waterpipe and/or cigarette smoker and DDT were the independent predictors of the number of traffic crashes in Poisson regression model. If the increased risk of RTC among waterpipe or cigarette smokers is seen in other studies, it would be beneficial to promote tobacco cessation and control strategies through injury prevention initiatives.